Electron Density and Chemical Bonding II Theoretical Charge Density Studies - Stalke, Dietmar.; Stalke, Dietmar. (Structure and Bonding,, 2012)
T. Koritsanszky, A. Volkov, M. Chodkiewicz: New Directions in Pseudoatom-Based X-Ray Charge Density Analysis.- B. Dittrich, D. Jayatilaka: Reliable Measurements of Dipole Moments from Single-Crystal Diffraction Data and Assessment of an In-Crystal Enhancement.- B. Engels, Th. C. Schmidt, C. Gatti, T. Schirmeister, R.F. Fink: Challenging Problems in Charge Density Determination: Polar Bonds and Influence of the Environment.- S. Fux, M. Reiher: Electron Density in Quantum Theory.- K. Meindl, J.Henn: Residual Density Analysis.- C. Gatti: The Source Function Descriptor as a Tool to Extract Chemical Information from Theoretical and Experimental Electron Densities.